Subsidy competition and the role of firm ownership - Ferdinand Mittermaier (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
This paper addresses the role that foreign vs. domestic ownership of companies plays for governments in asymmetric countries' competition for a multinational's subsidiary. I argue that equilibrium subsidies as well as a foreign investor's location decision in policy competition between these countries critically depend on the ownership structure of incumbent firms. This shows that small countries with few national incumbents in an industry may be successful in attracting multinationals.
Keywords: F12; F23; H25; L13; 330; Subsidy competition; foreign direct investment; regional location